2023
DOI: 10.1002/art.42505
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Pyroptosis Triggered by Macrophage‐Derived Extracellular Vesicles in Chondrocytes Leading to Cartilage Catabolism in Osteoarthritis

Abstract: Objective The severity of osteoarthritis (OA) and cartilage degeneration is highly correlated with the development of synovitis, which is mediated by the activity of inflammatory macrophages. A better understanding of intercellular communication between inflammatory macrophages and chondrocytes should aid in the discovery of novel therapeutic targets. We undertook this study to explore the pathologic role of inflammatory macrophage extracellular vesicles (EVs) in cartilage degeneration. Methods Macrophages wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…They mediate proximal or distal cellular communication by transporting a variety of functional substrates associated with tissue homeostasis and disease [ 15 , 16 ]. Recent research showed that macrophage-derived EVs led to cartilage catabolism and synovial inflammation, supporting the important role of EVs in OA [ 17 ]. Furthermore, synovial fibroblasts delivered microRNAs(miRNAs) to chondrocytes through EVs to mediate chondrocyte function, indicating that the EVs delivery function may be a potential mechanism in OA progression [ 18 ].…”
Section: Introductionmentioning
confidence: 95%
“…They mediate proximal or distal cellular communication by transporting a variety of functional substrates associated with tissue homeostasis and disease [ 15 , 16 ]. Recent research showed that macrophage-derived EVs led to cartilage catabolism and synovial inflammation, supporting the important role of EVs in OA [ 17 ]. Furthermore, synovial fibroblasts delivered microRNAs(miRNAs) to chondrocytes through EVs to mediate chondrocyte function, indicating that the EVs delivery function may be a potential mechanism in OA progression [ 18 ].…”
Section: Introductionmentioning
confidence: 95%
“…The phospholipid bilayer on their surface exhibits recognition specificity, making EVs well-suited for precise biological marking and the transport of certain drugs ( Jeppesen et al., 2023 ). EVs represent an emerging field of research in skeletal repair, with the majority of published studies emerging within the last five years ( Yin et al., 2022 ; Ebata et al., 2023 ; Liu et al., 2023c ). Documentation of the efficacy of EVs in various organs and systems exists, and in osteoarthritis (OA), it has been observed that EVs derived from mesenchymal stem cells (MSCs) can inhibit inflammation, downregulate the levels of IL-1β, IL-6, and IL-8, and increase extracellular matrix synthesis, effectively alleviating pain ( Li et al., 2022 ).…”
Section: Treatment Of Aseptic Inflammationmentioning
confidence: 99%
“…M2 macrophages can turn into M1 macrophages, which cause inflammation. 73 In individuals with OA, macrophages deposit crystals in the synovium. Dead cells release ATP, which activates the NLRP3 inflammasome to produce IL-1β and IL-18.…”
Section: Pyroptosis and Synovium In Oamentioning
confidence: 99%
“…It has been discovered through research that the inflammatory extracellular vesicles from macrophages can trigger both canonical and non-canonical pyroptosis in chondrocytes, leading to cartilage breakdown. 73 , 80 , 81 The synovium plays a crucial role in providing essential nutrition to the avascular cartilage tissue, and synovitis, the inflammation of the synovial tissue, is a significant factor in the development of OA. When the synovial tissue undergoes pyroptosis, it releases pro-inflammatory cartilage degradation products into the synovial fluid, which causes inflammation in the surrounding synovium, leading to further degradation of chondrocytes.…”
Section: Interconnection Of Tissues and Cells Of Pyroptosismentioning
confidence: 99%
See 1 more Smart Citation